Petrogenesis and geodynamic evolution of the Kajan Neogene subvolcanic rocks, Nain, Central Iran - Golkaram, S.
tKajan subvolcanic rocks in the Urumieh–Dokhtar magmatic arc (UDMA), Central Iran, form a LateMiocene-Pliocene shallow-level intrusion. These subvolcanics correspond to a variety of intermediateand felsic rocks, comprising quartz diorite, quartz monzodiorite, tonalite and granite. These lithologies aremedium-K calc-alkaline, with SiO2(wt.%) varying from 52% (wt.%) to 75 (wt.%). The major element chem-ical data also show that MgO, CaO, TiO2, P2O5, MnO, Al2O3and Fe2O3define linear trends with negativeslopes against SiO2, whilst Na2O and K2O are positively correlated with silica. Contents of incompatibletrace elements (e.g. Ba, Rb, Nb, La and Zr) become higher with increasing SiO2, whereas Sr shows an oppo-site behaviour. Chondrite-normalized multi-element patterns show enrichment in LILE relative to HFSEand troughs in Nb, P and Ti. These observations are typical of subduction related magmas that formed inan active continental margin. The Kajan rocks show a strong affinity with calc-alkaline arc magmas, con-firmed by REE fractionation (LaN/YbN= 4.5–6.4) with moderate HREE fractionation (SmN/YbN= 1.08–1.57).The negative Eu anomaly (Eu/Eu* <1), the low to moderate Sr content (< 400 ppm) and the Dy/Yb valuesreflect plagioclase and hornblende (+- clinopyroxene) fractionation from a calc-alkaline melt Whole–rockSr and Nd isotope analyses show that the87Sr/86Sr initial ratios vary from 0.704432 to 0.705989, and the143Nd/144Nd initial ratios go from 0.512722 to 0.512813. All the studied samples have similar Sr-Nd iso-topes, indicating an origin from a similar source, with granite samples that has more radiogenic Sr andlow radiogenic Nd isotopes, suggesting a minor interaction with upper crust during magma ascent. TheKajan subvolcanic rocks plot within the depleted mantle quadrant of the conventional Sr-Nd isotopediagram, a compositional region corresponding to mantle-derived igneous rocks.